An Emotional Process Theory of How Subordinates Appraise, Experience, and Respond to Abusive Supervision Over Time - Oh, Jo K.; Farh, Crystal I. C. (Academy of Management Review, 2017)
With empirical research on abusive supervision flourishing, there is an increasing need for an integrative framework that accounts for how and why individuals vary in their perceptions, experiences, and responses to abuse over time. To address this need, we integrate theories of emotions to present a multiphase, episodic process model explaining how initial attributions and appraisals combine to give rise to three distinct emotions—anger, fear, and sadness—that, in turn, drive a range of behavioral responses. We build on this foundation to offer new propositions on how various person and situational factors combine at each phase to produce different emotional and behavioral pathways, and we further conceptualize how feedback loops linking the behavioral responses in one episode to the next can result in emotional modulations and increasing (or decreasing) trajectories of adaptation to abuse. We advance the abusive supervision literature by providing a dynamic framework that integrates and organizes existing research, offering new emotions-based explanations for why people exhibit a range of responses to abuse over time, and highlighting areas in need of future research that have the potential to provide a more complete understanding of abusive supervision and its implications for organizations.